Peningkatan Kemampuan Pemecahan Masalah Soal Cerita Operasi Hitung Campuran melalui Model Pembelajaran Assurance, Relevance, Interest, Assessment, Satisfaction (Arias) pada Siswa Sekolah Dasar - Lusiana Novita WS; Hartono Hartono; Matsuri Matsuri (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2019)
This research aim was to describe the implementation of Assurance, Relevance,Interest, Assessment, Satisfaction (ARIAS) learning model in the ability in solving wordproblems mixed operation of the third grade of an elementary school in Surakarta City at theacademic year of 2017/2018. The research subject were a teacher and 25 students of the thirdgrade of an elementary school in Surakarta City at the academic year of 2017/2018. The typeof research was classroom action research which was conducted in three cycles. Each cycleconsisted of four phases, there were planning, acting, observing, and reflecting. The data wasgathered by observation, interview, test, and documentation. The data was validated by usingsource triangulation, tecnique triangulation, and validity of content. The data was analyzed byusing critical analysis, comparative descriptive, and interactive analysis. The conclusion of thisresearch was the implementation of ARIAS learning model can improved the ability in solvingword problems mixed operation of the third grade of an elementary school in Surakarta City atthe academic year of 2017/2018.